Membentuk Karakter Peduli Lingkungan Dengan Pendidikan - Iqbal, Muhammad (Universitas Muhammadiyah Sumatera Utara, 2021)
There are many environmental issues that until now do not have many solutions yet in this country. The environment has always been a big issue in almost all urban areas. This is still a lots thing to do by peoples. To foster the character of environmental care which plays a major role in the welfare and sustainability of people's lives, then awareness must be built for each individual. One of them is through education. Education is a process of maturity. The lack of understanding and skills in preserving the environment makes vulnerable communities act to not pay attention to the preservation of the environment in which they live. Environmental Education must be provided by all components of society. Environmental education needs to be taught from an early age to form awareness of caring for the environment.